Probing the binding of the coumarin drugs using peptide fragments of DNA gyrase B protein - Garrido, Saulo Santesso [UNESP]; Scatigno, A. C.; Trovatti, E. [UNESP]; Carvalho, D. C. [UNESP]; Marchetto, Reinaldo [UNESP] (Wiley, 2005)
Bacterial DNA gyrase, has been identified as the target of several antibacterial agents, including the coumarin drugs. The coumarins inhibit the gyrase action by competitive binding to the ATP-binding site of DNA gyrase B (GyrB) protein. The high in vitro inhibitory potency of coumarins against DNA gyrase reactions has raised interest in studies on coumarin-gyrase interactions. In this context, a series of low-molecular weight peptides, including the coumarin resistance-determining region of subunit B of Escherichia coli gyrase, has been designed and synthesized. The first peptide model was built using the natural fragment 131-146 of GyrB and was able to bind to novobiocin (K a = 1.8 ± 0.2 × 105/M) and ATP (Ka = 1.9 ± 0.4 × 103/M). To build the other sequences, changes in the Arg136 residue were introduced so that the binding to the drug was progressively reduced with the hydrophobicity of this residue (Ka = 1.3 ± 0.1 × 105/M and 1.0 ± 0.2 × 105/M for Ser and His, respectively). No binding was observed for the change Arg136 to Leu. In contrast, the binding to ATP was not altered, independently of the changes promoted. On the contrary, for peptide-coumarin and peptide-ATP complexes, Mg2+ appears to modulate the binding process. Our results demonstrate the crucial role of Arg 136 residue for the stability of coumarin-gyrase complex as well as suggest a different binding site for ATP and in both cases the interactions are mediated by magnesium ions. Copyright Blackwell Munksgaard, 2005.
Keywords: Affinity chromatography; Coumarins; DNA gyrase; Fluorescence; Peptide synthesis; Quenching; coumarin anticoagulant; DNA topoisomerase (ATP hydrolysing) B; novobiocin; affinity chromatography; binding site; complex formation; DNA supercoiling; drug binding; enzyme activity; enzyme subunit; nonphotochemical quenching; peptide synthesis; priority journal; protein binding; target cell; Adenosine Triphosphate; Amino Acid Sequence; Arginine; Binding Sites; Binding, Competitive; Chromatography, Affinity; DNA Gyrase; Drug Design; Escherichia coli Proteins; Magnesium; Molecular Sequence Data; Novobiocin; Peptide Fragments; Bacteria (microorganisms); Escherichia coli